HPLC METHOD FOR SIMULTANEOUS DETERMINATION OF KETOPROFEN AND PRESERVATIVES IN GEL FORMULATION - Tsvetkova, Boyka; Peikova, Lily (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: The aim of presented study was to develop a high-performance liquid chromatography (HPLC) method with UV detection for simultaneous determination of ketoprofen, methyl paraben and propyl paraben in a gel formulation. Methods: The chromatography was carried out on a C18 (250 mm x 4.6 mm, 10 Î¼m) column with methanol, acetonitrile and 1.5 % sodium acetate solution (15:35:50 v/v/v) as mobile phase, at a flow rate of 1.0 ml/min, with detection at 240 nm. Results: Under these chromatographic conditions, the obtained retention times were approximately 2.41 min for methyl paraben, 3.33 min for propyl paraben and 7.41 min for ketoprofen. Analytical parameters specificity, linearity, accuracy, precision and robustness were determined by validation procedure and found to be satisfactory. Conclusion: Overall, the proposed method was found to be simple, rapid, precise and accurate for quality control of ketoprofen in the presence of preservatives in gel formulation.